2017
DOI: 10.4012/dmj.2016-219
|View full text |Cite
|
Sign up to set email alerts
|

Remineralizing effect of cold plasma and/or bioglass on demineralized enamel

Abstract: This study investigated the combining effect of cold plasma and bioglass-phosphoric acid paste on demineralized enamel. Fifty bovine incisors' enamel specimens were challenged by a demineralization solution of pH 4.47 for 72 h. Specimens were divided into five groups: (I) Control, demineralized enamel (C); (II) Demineralized enamel treated with fluoride varnish (F); (III) Cold plasma application to demineralized enamel (P); (IV) Demineralized enamel treated with bioglass paste (B); (V) Application of bioglass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Surface microhardness of the enamel tissue decreased after the demineralization procedure and increased after application of bioactive glass. The value of microhardness was found to be higher in bioactive glass group when compared to the control group or application of other agents [19][20][21]23,29,38]. A study reported the recovery rate of microhardness on demineralized enamel surface after treatment with bioactive glass was 28.8% [21].…”
Section: Zhang Et Al (2019) [37]mentioning
confidence: 99%
See 2 more Smart Citations
“…Surface microhardness of the enamel tissue decreased after the demineralization procedure and increased after application of bioactive glass. The value of microhardness was found to be higher in bioactive glass group when compared to the control group or application of other agents [19][20][21]23,29,38]. A study reported the recovery rate of microhardness on demineralized enamel surface after treatment with bioactive glass was 28.8% [21].…”
Section: Zhang Et Al (2019) [37]mentioning
confidence: 99%
“…A study reported the recovery rate of microhardness on demineralized enamel surface after treatment with bioactive glass was 28.8% [21]. Further investigation showed that a combination of bioglass paste and cold plasma had a synergistic effect on increasing the surface microhardness of demineralized enamel [29]. Apart from assessing microhardness, the mean carious lesion depth in specimens treated with bioactive glass were significantly lower than those of specimens without bioactive glass treatment [20,26,38].…”
Section: Zhang Et Al (2019) [37]mentioning
confidence: 99%
See 1 more Smart Citation
“…They were first sectioned to remove their buccal surfaces using a water cooled diamond saw (Imicryl, Konya, Turkey), giving one enamel specimen per tooth. A total of 40 sound enamel were then embedded in pre-cut metal cylinders using cold acrylic resin (Imicryl, Konya, Turkey) [27]. The enamel surfaces were flattened and polished using 400-, 600-, 800-, and 1200-grit sandpaper [28].…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] Bioactive glass reacts with saliva to release Ca 2+ , Na + , and PO 4 3− ions. 18 It forms a layer highly reach in calcium, phosphate and silica attached to the enamel surface and thus has the potential to remineralize the tooth structure. 19 Many laser types are also used for preventive purposes in dentistry.…”
Section: Introductionmentioning
confidence: 99%